2020
DOI: 10.3350/cmh.2020.0169
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and liver cancer

Abstract: Autophagy is a highly conserved catabolic process that degrades cytosolic proteins and organelles via formation of autophagosomes that fuse with lysosomes to form autolysosomes, whereby autophagic cargos are degraded. Numerous studies have demonstrated that autophagy plays a critical role in the regulation of liver physiology and homeostasis, and impaired autophagy leads to the pathogenesis of various liver diseases such as viral hepatitis, alcohol associated liver diseases (AALD), non-alcoholic fatty liver di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 136 publications
(176 reference statements)
0
35
0
Order By: Relevance
“…On the contrary, autophagy contributes to survival of cancer cells by providing them with nutrients required for increased energy metabolism and removing toxic reactive oxygen radicals and mis-folded proteins [ 47 , 48 ]. Thus, inhibition of autophagy can render cancer cells susceptible to cytotoxic substances.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, autophagy contributes to survival of cancer cells by providing them with nutrients required for increased energy metabolism and removing toxic reactive oxygen radicals and mis-folded proteins [ 47 , 48 ]. Thus, inhibition of autophagy can render cancer cells susceptible to cytotoxic substances.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily on the strength of antiviral treatment (AVT) using oral nucleos(t)ide analogues (NUCs) suppressing viral replication, both virological and biochemical remission could be easily achieved in most of treated patients, where necro‐inflammation and resultant fibrosis could be significantly improved 6–8 . Nevertheless, AVT decreases but does not eliminate the risk of HCC development completely, primarily owing to complex direct and indirect mechanisms of hepato‐carcinogenesis 9–13 …”
Section: Introductionmentioning
confidence: 99%
“…mTOR inhibitors have considerable appeal in HCC patients undergoing LT, as they may prevent the proliferation of cancer cells ( Jung et al, 2018 ). Recent evidence has shown that the mTOR pathway is expressed at a higher level in HCC cells, and tumor regression was achieved in HCC-harboring animals by treatment with rapamycin ( Lee et al, 2020a ; Chao et al, 2020 ; Ferrin et al, 2020 ). Previous studies demonstrated that mTOR inhibitors may reduce the recurrence of HCC after LT ( Grigg et al, 2019 ), although most of these studies compared an mTOR inhibitor plus a low dose of TAC and a regular dose of TAC only.…”
Section: Introductionmentioning
confidence: 99%